Enteric Tube Placement and Management: Tips for Interventional Radiologists - Mittal, Alok K.; Gala, Kunal; Hadidi, Aymen Al; Vuthaluru, Srineil (Digestive Disease Interventions, 2024)
There is a significant risk of malnutrition and aspiration among hospitalized patients, particularly the elderly, patients with head and neck malignancy, and those with a chronic debilitating disease. Enteral feeding is preferred over parenteral feeding for patients with functional gastrointestinal tracts but who have impaired swallowing due to its cost-effectiveness, lesser complications, and theoretical benefits such as preserving mucosal architecture and gut-associated lymphoid tissue. While nasogastric and nasojejunal tubes address short-term feeding needs, long-term enteral feeding tubes are crucial for patients requiring nutritional support beyond 4 weeks. Enteric tube placement can be performed surgically, endoscopically, or radiologically, with radiologically inserted gastrostomy emerging as a safe and effective method. This review article discusses various interventional radiological techniques for enteral feeding, including percutaneous gastrostomy, gastrojejunostomy, jejunostomy tube placement, and gastrointestinal tract decompression procedures like cecostomy. It covers procedural considerations, patient selection criteria, technical aspects, and outcomes, drawing on current evidence and clinical experience. The review also addresses emerging trends, advancements, and future directions in interventional radiology for enteral feeding and gastrointestinal tract decompression, aiming to contribute to the ongoing evolution of clinical practice and patient care. Key recommendations from international guidelines are summarized, emphasizing individualized risk assessment for optimal enteral feeding strategies.
Keywords: gastrostomy; enteric tube; jejunostomy; cecostomy